2011
DOI: 10.1111/j.1744-7909.2010.01010.x
|View full text |Cite
|
Sign up to set email alerts
|

WBC27, an Adenosine Tri‐phosphate‐binding Cassette Protein, Controls Pollen Wall Formation and Patterning in Arabidopsis

Abstract: In flowering plants, the exine components are derived from tapetum. Despite its importance to sexual plant reproduction, little is known about the translocation of exine materials from tapetum to developing microspores. Here we report functional characterization of the arabidopsis WBC27 gene. WBC27 encodes an adenosine tri-phosphate binding cassette (ABC) transporter and is expressed preferentially in tapetum. Mutation of WBC27 disrupted the exine formation. The wbc27 mutant microspores began to degenerate onc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
62
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 52 publications
1
62
0
Order By: Relevance
“…Many recent reports revealed the mechanism of biosynthesis and transport of pollen wall precursors in Arabidopsis and showed that the pollen wall is important for pollen development and protection (van der Meer et al, 1992;Matsuda et al, 1996;Aarts et al, 1997;Morant et al, 2007;de Azevedo Souza et al, 2009;Dobritsa et al, 2009Dobritsa et al, , 2010Quilichini et al, 2010;Xu et al, 2010;Choi et al, 2011;Dou et al, 2011). By contrast, studies on pollen coat lipids were mostly centered on pollen-stigma interactions, such as the self-incompatibility response and pollen hydration (Preuss et al, 1993;Piffanelli et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many recent reports revealed the mechanism of biosynthesis and transport of pollen wall precursors in Arabidopsis and showed that the pollen wall is important for pollen development and protection (van der Meer et al, 1992;Matsuda et al, 1996;Aarts et al, 1997;Morant et al, 2007;de Azevedo Souza et al, 2009;Dobritsa et al, 2009Dobritsa et al, , 2010Quilichini et al, 2010;Xu et al, 2010;Choi et al, 2011;Dou et al, 2011). By contrast, studies on pollen coat lipids were mostly centered on pollen-stigma interactions, such as the self-incompatibility response and pollen hydration (Preuss et al, 1993;Piffanelli et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…In many organisms, including animals, insects, fungi, and plants, ABCG subfamily members are reported to be involved in lipid transport (Li and Prinz, 2004;Velamakanni et al, 2007;Kang et al, 2011), and the deletion of some members of the transporter family results in lipid-related diseases, growth defects, and sterility (Berge et al, 2000;Bird et al, 2007;Luo et al, 2007;Panikashvili et al, 2007;Ukitsu et al, 2007;Quilichini et al, 2010;Xu et al, 2010;Choi et al, 2011;Dou et al, 2011). Plants are highly enriched in a number of ABCG transporters, but only several of these have been studied to date.…”
Section: Introductionmentioning
confidence: 99%
“…Some plant ABCG proteins have been reported to contribute to the synthesis of extracellular barriers. In Arabidopsis, ABCG11 (Cuticular Defect and Organ Fusion1/DESPERADO/White-Brown Complex11; Bird et al, 2007;Panikashvili et al, 2007Panikashvili et al, , 2010, ABCG12 (Eceriferum5/WBC12; Pighin et al, 2004), ABCG13 (Panikashvili et al, 2010), ABCG29 (Alejandro et al, 2012), ABCG32 (Bessire et al, 2011), and ABCG26 (WBC27; Xu et al, 2010;Quilichini et al, 2010Quilichini et al, , 2014Choi et al, 2011;Dou et al, 2011) have been shown to be involved in transport of lipidic compounds. Notably, it has been reported that these ABCG proteins have a broad substrates spectrum (for example, ABCG11 transports both cutin and wax monomers, and ABCG13 and ABCG32 mainly transport cutin monomers, whereas ABCG12 mainly transports wax precursors, and ABCG29 mainly transports monolignol).…”
mentioning
confidence: 99%
“…Sporopollenin precursors are synthesized mainly in tapetal cells and transported to the microspore surface by the involvement of many genes in which mutations often cause strong defects in exine development. These genes include: MALE STERILITY2 (MS2) (Aarts et al, 1997), FACELESS POLLEN1 (FLP1) (Ariizumi et al, 2003), NO EXINE FORMATION1 (NEF1) (Ariizumi et al, 2004), CYP703A2 (Morant et al, 2007), ACYL-CoA SYNTHETASE5 (ACOS5) (de Azevedo Souza et al, 2009), LESS ADHERENT POLLEN3 (LAP3), LAP5/POLYKETIDE SYNTHASE B (PKSB), LAP6/POLYKETIDE SYNTHASE A (PKSA) (Dobritsa et al, 2009a;Dobritsa et al, 2010;Kim et al, 2010), CYP704B1 (Dobritsa et al, 2009b), DIHYDROFLAVONOL 4-REDUCTASE-LIKE1 (DRL1)/ TETRAKETIDEa-PYRONE REDUCTASE2 (TKPR2) (Tang et al, 2009;Grienenberger et al, 2010), TKPR1 , and a member of ATPbinding cassette transporter gene ABCG26 (Quilichini et al, 2010;Choi et al, 2011;Dou et al, 2011;Kuromori et al, 2011). Although many of these genes are specifically expressed in tapetal cells, it has been proposed that microspores also synthesize and secrete sporopollenin at the initial stage of exine development in tetrads (Wallace et al, 2011).…”
mentioning
confidence: 99%